Psychological features of the experience of separation anxiety in the conditions of medical rehabilitation - Гайдучик, П. Д. (Psychological Counseling and Psychotherapy, 2018)
The article is devoted to the identification specifics analysis of the separation anxiety experience in the medical rehabilitation conditions. The identification determination of a personality’s successfully completed separation has been grounded and the identification content of the separation anxiety experience of patients undergoing treatment in the stationary departments has been empirically verified. The differences of personality characteristics of people with different identity levels have been empirically determined; the psychological profiles (autonomic anxiety, protective egocentrism, frustration depressiveness, selfless activity and emotional dominance) for respondents with different identity levels have been outlined.